Investigation on mining subsidence over Appin–West Cliff Colliery using time-series SAR interferometry. Issue 5 (4th March 2018) - Du, Zheyuan; Ge, Linlin; Ng, Alex Hay-Man; Li, Xiaojing
ABSTRACT: Advanced Time Series InSAR (ATS-InSAR) generally refers to those TS-InSAR methods with an external distributed scatterer selection module, e.g. SqueeSAR™, and GEOS-ATSA (Advanced Time-Series Analysis). It is being known as a very efficient tool for monitoring ground deformation over suburban or non-urban regions with great success. However, research conducted using C-band Envisat-based ATS-InSAR failed to produce reasonable outcome within Appin Colliery primarily due to the underground mining effect, which is located in the southeastern corner of the Southern Coalfield, New South Wales, Australia; thus, the general underground mining pattern cannot be formed. This work presents a modified ATS-InSAR method for mapping the ground deformation over underground mining region. More specifically, in order to achieve the best outcome, a modified measurement scatterer (MS) pixel selection method is introduced by including less reliable MS pixels through an Inverse Distance Weighted-based integration method. In addition, the proposed method is also applied to C-band Sentinel-1 image stacks for testing purpose, and the final result proved to be efficient to offer sufficient information to the mining industry and government for risk management purpose.